The long journey: Perspectives on the coordination of Chilean higher education - Salazar, Jose M.; Leihy, Peodair S. (Education Policy Analysis Archives, 2017)
It is fairly established that Chilean higher education presents a high level of Habermasian “privatism”, as long labeled by José Joaquin Brunner, being among the world's most privatized systems in terms of who pays, who is held to benefit directly from its action and who controls it. Less clear, however, is the contribution of public policy to this state of affairs. The systematic analysis of state action in the field of tertiary education is an ongoing task in Chile, not least given the revolutionary transformation experienced during recent decades. This study offers new possibilities of analysis for the Chilean case. Supported by the methodological analysis of Neil Smelser, it lays out an integrated framework that observes the progressive change in policy with regard to the interactions undergone by its principal dimensions (access, financing and quality, among others).  Upon such a base, the study traces the trajectory of two regimes of sector regulation that become incorporated in three stages, initially by lack of maintenance of the regulatory framework, then by government decision. In the end emerge the conditions for sector policy in a new era, one in which the development of the universities might again come to depend fundamentally on the state.